O processo de cobrança e seus impactos na arrecadação municipal: uma análise comparativa entre o Município de Fortaleza e o Estado do Ceará - Nascimento, Rafael Freitas do (2023)
The Study investigates the main sources of municipal revenue and the tax collection process of the city of Fortaleza to evaluate the performance of local revenue vis-à-vis that obtained via state transfers between January 2020 and December 2022. Autoregressive vector models for local tax collection and state transfers, as well as for the Service Tax (ISS) and the Tax on the Circulation of Goods and Services (ICMS) are estimated and allow us to verify: i) evidence of cointegration between local own revenues and of state transfers, corroborated by the stationarity of the indicator defined as the ratio between the two sources of revenue, but; ii) lack of cointegration between municipal ISS collection and state ICMS, corroborated by a non-stationary dynamic of the indicator defined by the ratio between ISS and ICMS. Taken together, these results suggest that innovations in the Fortaleza city council's collection process had a greater impact on ISS collection, which has a greater potential for growth in the recent period, even in terms relative to the state ICMS. Another factor that impacted the transfer of the ICMS Share was the loss of index for the Municipality of Fortaleza, in 2021 when the index fell from 33% to 27%, contributing to an unfavorable trend for the ICMS Share.